Heavy metal uptake and translocation by Dipterocarpus verrucosus from sewage sludge contaminated soil - Sundara Rajoo, Keeren; Abdu, Arifin; Karam Singh, Daljit Singh; Abdul Hamid, Hazandy; Jusop, Shamshuddin; Wong, Wan Zhen (Science Publications, 2013)
Sewage sludge or biosolids is the solid waste that has been left after wastewater is treated in a domestic wastewater treatment facility. The most common way of sludge disposal is to dispose it on the land, sea or air (incineration). However, these methods are not environment-friendly, costly and time consuming that requires expertise and knowledge. An ideal way to manage sewage sludge is to use it as a soil amendment in agricultural land due to it's high organic matter and other base cations. Sewage sludge contains high levels of heavy metals such as lead, cadmium and zinc that can be harmful to both plants and the environment. Hence, these metals need to be removed before the sewage sludge is used as a soil amendment. The objective of this study was to assess the potential of Dipterocarpus verrucosus to uptake and translocate heavy metals from sewage sludge contaminated soil. The D.verrucosus seedlings were planted on six different planting media; Control (100% soil), T1 (80% soil and 20% sewage sludge), T2 (60% soil and 40% sewage sludge), T3 (40% soil and 60% sewage sludge), T4 (20% soil and 80% sewage sludge) and T5 (100% sewage sludge) for the duration of 16 weeks. The growth performance, of height of D.verrucosus was measured using diameter tape, while the basal diameter was measured using a venier caliper for every two weeks for a period of 16 weeks. The plant biomass was determined using a destructive sampling method. Plant samples were collected after harvest and soil samples were collected before and after planting. The Atomic Absorbtion Spectrophotometer (AAS) was used to determine the concentration of heavy metals in the planting media and the plant parts (leaves, stem and roots). The highest plant biomass was recorded in the T1 growth media of 20% sewage sludge and 80% soil. D.verrucosus plant was able to remove heavy metals of Cd, Cu, Pb, Fe and Zn effectively. The highest concentration of heavy metal in the roots of the D.verrucosus plant was Fe, recorded in the T5 growth media (1879.75 ppm). The highest accumulation of Zn (68.47 ppm) in D.verrucosus was recorded in the stem of D.verrucosus in the T5 growth media whereas the stem of the D.verrucosus in T3 recorded the highest Cd accumulation (2.85 ppm). The highest Pb uptake was recorded in the roots of D.verrucosus in T5 (37.3 ppm), while the lowest accumulation of Pb was noted in the stem of the D.verrucosus in Control (23.49 ppm). For Cd, the highest translocation factor (TF) (4.01) was recorded in T1. The lowest Bioconcentration Factor (BCF) for Cu was recorded at T5 (0.22). The highest TF for Lead was recorded in control (2.22) while the lowest was in T1 (1.64). The BCF for Zn was lowest at T3 treatment (0.16). The D.verrucosus plant was found to be suitable for taking up heavy metals from sewage sludge especially Cd, Zn, Cu and Pb. The roots of D.verrucosus are ideal in removing and storing Fe, while the stem of the D.verrucosus plant is ideal for the uptake and accumulation of Zn. However, more studies need to be conducted, especially in field conditions, in order to optimize the potential of the D.verrucosus plant as a phytoremediator.